Multimedia Interactive Learning in Science Subjects for Grade Fourth Elementary School Students - Mega Putri Islamyati; Ida Bagus Surya Manuaba (Universitas Pendidikan Ganesha, 2021)
Teaching materials and online learning outcomes that are less than optimal affect the learning process. Students need visualization that can help concrete understanding of the material, especially in implementing online learning. This study aimed to develop interactive multimedia learning in science subjects according to the validation of expert tests and individual trials. This development research applies the DDD-E model (Decide, Design, Develop, Evaluate). The method used to collect data is a questionnaire equipped with observations and interviews. The data analysis used is quantitative and qualitative descriptive analysis. The subject of this development research is interactive learning multimedia. Then a review is carried out from subject content expert validators, instructional design experts, learning media experts, and individual trials on students. The results of data analysis based on validation by subject matter content experts obtained a percentage score of 96.15% with very good qualifications, instructional design experts obtained a score percentage of 87.5% with good qualifications, learning media experts obtained a percentage score of 93.00% with very good qualifications, and the results of the review of 3 students in individual trials obtained a percentage score of 91.66% with very good qualifications. Based on the results obtained, it can be concluded that the interactive learning multimedia developed is very feasible in science learning for sixth-grade elementary school students.